Women’s Rights and Humanitarian Emergencies in Nigeria - Adeyanju Faith O.; Adeyanju Joseph B.; Ogunseye Inioluwa I. (Covenant University Journal of Politics and International Affairs, 2023)
This paper examines women’s rights during humanitarian emergencies, with particular reference to North-East Nigeria. In highly patriarchal societies such as Nigeria, women’s rights are deeply rooted in existing customs, practices, and religious beliefs which undermine the fundamental human rights of women and hinders the full realization of gender equality. However, in complex humanitarian emergencies as in North-East Nigeria, research shows that women experience gross human rights violations as a result of their vulnerability. This paper employs the qualitative research approach, using relevant documents, observation and focus group discussions as sources of data, analyzed using content analysis. Within the state fragility theoretical framework, this study concludes that the Nigerian government has not shown full commitment to prevent and investigate human rights breaches by failing to address the violations of women’s rights. The paper therefore recommends the need for pragmatic and gender-sensitive measures regarding the subject matter.